Telecommunications Consumer Protections Are Vital - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2018)
Papers in the March 2018 issue of the Journal cover advances in telecommunications technologies and regulation, historical events, and book reviews. Looking more widely, the Australian Government has responded to the increase in complaints about telecommunications services by ordering yet another review. Telecommunications consumers are rightly concerned that access to reliable and modern telecommunications is a key aspect of life today. Telecommunications consumer protections are vital and there needs to be a timely response to the rapid rise in complaints that was accurately predicted four years ago by industry experts. The Journal would welcome contributions on this and other topics.